Transcriptomic identification of starfish neuropeptide precursors yields new insights into neuropeptide evolution. Issue 2 (February 2016) - Semmens, Dean C.; Mirabeau, Olivier; Moghul, Ismail; Pancholi, Mahesh R.; Wurm, Yannick; Elphick, Maurice R.
Abstract : Neuropeptides are evolutionarily ancient mediators of neuronal signalling in nervous systems. With recent advances in genomics/transcriptomics, an increasingly wide range of species has become accessible for molecular analysis. The deuterostomian invertebrates are of particular interest in this regard because they occupy an 'intermediate' position in animal phylogeny, bridging the gap between the well-studied model protostomian invertebrates (e.g. Drosophila melanogaster, Caenorhabditis elegans ) and the vertebrates. Here we have identified 40 neuropeptide precursors in the starfish Asterias rubens, a deuterostomian invertebrate from the phylum Echinodermata . Importantly, these include kisspeptin-type and melanin-concentrating hormone-type precursors, which are the first to be discovered in a non-chordate species. Starfish tachykinin-type, somatostatin-type, pigment-dispersing factor-type and corticotropin-releasing hormone-type precursors are the first to be discovered in the echinoderm/ambulacrarian clade of the animal kingdom. Other precursors identified include vasopressin/oxytocin-type, gonadotropin-releasing hormone-type, thyrotropin-releasing hormone-type, calcitonin-type, cholecystokinin/gastrin-type, orexin-type, luqin-type, pedal peptide/orcokinin-type, glycoprotein hormone-type, bursicon-type, relaxin-type and insulin-like growth factor-type precursors. This is the most comprehensive identification of neuropeptide precursor proteins in an echinoderm to date, yielding new insights into the evolution of neuropeptide signalling systems. Furthermore, these data provide a basis for experimental analysis of neuropeptide function in the unique context of the decentralized, pentaradial echinoderm bauplan.